Tuberculosis and HIV/AIDS-attributed mortalities and associated sociodemographic factors in Papua New Guinea: evidence from the comprehensive health and epidemiological surveillance system - Chalapati Rao; Willie Pomat; Tony Okely; Bang Nguyen Pham; Norah Abori; Vinson D Silas; Ronny Jorry (BMJ Open)
Objective Tuberculosis (TB) and HIV/AIDS are public health concerns in Papua New Guinea (PNG). This study examines TB and HIV/AIDS mortalities and associated sociodemographic factors in PNG.Method As part of a longitudinal study, verbal autopsy (VA) interviews were conducted using the WHO 2016 VA Instrument to collect data of 926 deaths occurred in the communities within the catchment areas of the Comprehensive Health and Epidemiological Surveillance System from 2018 to 2020.InterVA-5 cause of deaths analytical tool was used to assign specific causes of death (COD). Multinomial logistic regression analyses were conducted to identify associated sociodemographic factors, estimate adjusted ORs (AOR), 95% CIs and p values.Result TB and HIV/AIDS were the leading CODs from infectious diseases, attributed to 9% and 8% of the total deaths, respectively.Young adults (25–34 years) had the highest proportion of deaths from TB (20%) and the risk of dying from TB among this age group was five times more likely than those aged 75+ years (AOR: 5.5 (95% CI 1.4 to 21.7)). Urban populations were 46% less likely to die from this disease compared rural ones although the difference was not significant (AOR: 0.54 (95% CI 0.3 to 1.0)). People from middle household wealth quintile were three times more likely to die from TB than those in the richest quintile (AOR: 3.0 (95% CI 1.3 to 7.4)).Young adults also had the highest proportion of deaths to HIV/AIDS (18%) and were nearly seven times more likely to die from this disease compared with those aged 75+years (AOR: 6.7 (95% CI 1.7 to 25.4)). Males were 48% less likely to die from HIV/AIDS than females (AOR: 0.52 (95% CI 0.3 to 0.9)). The risk of dying from HIV/AIDS in urban population was 54% less likely than their rural counterparts (AOR: 0.46 (95% CI 0.2 to 0.9)).Conclusion TB and HIV/AIDS interventions are needed to target vulnerable populations to reduce premature mortality from these diseases in PNG.